Magnetic Resonance Image-Guided Radiotherapy (MRIgRT): A 4.5-Year Clinical Experience. Issue 11 (November 2018) - Henke, L.E.; Contreras, J.A.; Green, O.L.; Cai, B.; Kim, H.; Roach, M.C.; Olsen, J.R.; Fischer-Valuck, B.; Mullen, D.F.; Kashani, R.; Thomas, M.A.; Huang, J.; et al.
Abstract: Aims: Magnetic resonance image-guided radiotherapy (MRIgRT) has been clinically implemented since 2014. This technology offers improved soft-tissue visualisation, daily imaging, and intra-fraction real-time imaging without added radiation exposure, and the opportunity for adaptive radiotherapy (ART) to adjust for anatomical changes. Here we share the longest single-institution experience with MRIgRT, focusing on trends and changes in use over the past 4.5 years. Materials and methods: We analysed clinical information, including patient demographics, treatment dates, disease sites, dose/fractionation, and clinical trial enrolment for all patients treated at our institution using MRIgRT on a commercially available, integrated 0.35 T MRI, tri-cobalt-60 device from 2014 to 2018. For each patient, factors including disease site, clinical rationale for MRIgRT use, use of ART, and proportion of fractions adapted were summated and compared between individual years of use (2014–2018) to identify shifts in institutional practice patterns. Results: Six hundred and forty-two patients were treated with 666 unique treatment courses using MRIgRT at our institution between 2014 and 2018. Breast cancer was the most common disease, with use of cine MRI gating being a particularly important indication, followed by abdominal sites, where the need for cine gating and use of ART drove MRIgRT use. One hundred and ninety patients were treated using ART in 1550 fractions, 67.6% (1050) of which were adapted. ART was primarily used in cancers of the abdomen. Over time, breast and gastrointestinal cancers became increasingly dominant for MRIgRT use, hypofractionated treatment courses became more popular, and gastrointestinal cancers became the principal focus of ART. Discussion: MRIgRT is widely applicable within the field of radiation oncology and new clinical uses continue to emerge. At our institution to date, applications such as ART for gastrointestinal cancers and accelerated partial breast irradiation (APBI) for breast cancer have become dominant indications, although this is likely to continue to evolve. Highlights: We report single-institution clinical use patterns of magnetic resonance image-guided radiotherapy (MRIgRT) from 2014–2018. In 4.5 years, 642 patients received 666 unique treatment courses, including 1550 fractions of adaptive radiotherapy (ART). The primary reasons for MRIgRT use were: 1. Improved setup accuracy 2. Cine MR gating 3. Online and offline ART. Over 4.5 years, gastrointestinal cancers became the main indication for ART and RT courses became shorter (≤12 fractions). The changes in patterns of use observed here can guide best clinical use for other institutions implementing MRIgRT.